Effect of Long-Term Polytrauma on Ventilator-Induced Diaphragmatic Dysfunction in a Piglet Model. Issue 4 (October 2019) - Breuer, Thomas; Bruells, Christian S.; Horst, Klemens; Thiele, Christoph; Hildebrand, Frank; Linnartz, Stephan; Siegberg, Tom; Frank, Nadine; Gayan-Ramirez, Ghislaine; Martin, Lukas; Ostareck, Dirk H.; Marx, Gernot; et al.
ABSTRACT: Introduction: Mechanical ventilation is known to activate oxidative stress and proteolytic pathways in the diaphragm. Trauma by inducing inflammation and activating proteolytic pathways may potentiate the effects of mechanical ventilation on the diaphragm. In a blunt chest trauma with concomitant injuries we tested the hypothesis that trauma via inflammation further activates the proteolytic pathways and worsens atrophy in the diaphragm. Material and Methods: Piglets were separated into two groups and underwent 72 h of mechanical ventilation. One group received a polytrauma (PT) by unilateral femur fracture, blunt chest trauma with lung contusion, laparotomy with standardized liver incision, and a predefined hemorrhagic shock. The second mechanically ventilated group (MV) did not receive any trauma. A non-ventilated group (Con) served as control. Diaphragmatic fiber dimensions, Western Blot analyses of proteolytic pathways, and lipid peroxidation and messenger ribonucleic acid (mRNA) levels of cytokines and nuclear factor kappa b subunit p65 were measured. Results: Active Caspase-3 was significantly increased in MV ( P = 0.019), and in PT ( P = 0.02) compared with Con. Nuclear factor kappa b subunit p65, was upregulated in PT ( P = 0.010) compared with Con. IL-6 mRNA increased significantly in PT compared with Con ( P = 0.0024) but did not differ between Con and MV. Conclusion: Trauma and mechanical ventilation induced proteolysis and atrophy in the diaphragm, but only polytrauma induced an inflammatory response in the diaphragm. The additional traumatic inflammatory stimulus did not increase the levels of the prementioned variables. These data underline that inflammation is not a major contributor to ventilator-induced diaphragmatic dysfunction. Trial registry number: AZ 84–02.04.2014.A265 (Landesamt für Natur-, Umwelt- und Verbraucherschutz, LANUV NRW, Germany). Abstract : Supplemental Digital Content is available in the text